2022
DOI: 10.1002/fsn3.2922
|View full text |Cite
|
Sign up to set email alerts
|

Calculator for inadequate micronutrient intake for Ethiopia (CIMI‐Ethiopia): Validation of the software for lactating mothers and their children under 2 years

Abstract: Early identification of inadequate intake of nutrients from a person's diet is usually crucial to prevent the development of micronutrient malnutrition. However, there is no single dietary assessment tool for Ethiopia that can assess the nutrient intake of a person from the type of food she or he consumed with a given amount. Therefore, the Calculator for Inadequate Micronutrient Intake (CIMI) application was adapted in consideration of food and nutrition contexts in Ethiopia and validated for its suitability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 28 publications
3
6
3
Order By: Relevance
“…Vitamin A intake inadequacy was prevalent among 86.7% of lactating mothers, according to this study. This is comparable to studies conducted in Ethiopia ( 13 ), Niger ( 12 ), and Bangladesh ( 8 ). In contrast, this study finding is lower than studies conducted in Bahir Dar City, Ethiopia ( 14 ), Zambia ( 11 ), China ( 45 ), and California ( 10 ), and higher than reports from studies conducted in Nigeria ( 46 ), Indonesia ( 41 ), Thailand ( 44 ) and Iran ( 43 ).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Vitamin A intake inadequacy was prevalent among 86.7% of lactating mothers, according to this study. This is comparable to studies conducted in Ethiopia ( 13 ), Niger ( 12 ), and Bangladesh ( 8 ). In contrast, this study finding is lower than studies conducted in Bahir Dar City, Ethiopia ( 14 ), Zambia ( 11 ), China ( 45 ), and California ( 10 ), and higher than reports from studies conducted in Nigeria ( 46 ), Indonesia ( 41 ), Thailand ( 44 ) and Iran ( 43 ).…”
Section: Discussionsupporting
confidence: 84%
“…When compared to all other micronutrients, nearly all mothers (98.4%) undoubtedly failed to meet the RDA for vitamin C. The finding corresponded to the Niger result ( 12 ); lower reports were obtained in Ethiopia ( 13 , 14 ), Zambia ( 11 ), Bangladesh ( 8 ), Thailand ( 44 ), China ( 45 ), Indonesia ( 41 ), Iran ( 43 ), and California ( 10 ). This could be explained by the variation in fruit and vegetable consumption, as the current study showed quite low fruit and vegetable consumption.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations